Finding One’s Place to Be and Pee: Examining Intersections of Gender-Dis/ability in Washroom Signage - Castrodale, Mark Anthony; Lane, Laura (Atlantis, 2015)
In this article, we explore power relations in space by examining how the intersections of gender and disability are discursively represented in washroom signage. To do so, we analyze various washroom signs found in public spaces and airports that the authors encountered in their travels in North America, Hawaii, and Europe and how they depict bodies in spaces, times, and contexts. We discuss dominant discursive representations of gender and disability in relation to constructions of family, caregiving roles, and cultural location. We argue that washroom signs constitute gendered and disabled subjects and mediate their subjectivities. Furthermore, they function to regulate bodies in space, influencing notions of who belongs, who belongs where, and how different bodies are de(valued).